SnO2 nanoparticles as effective adsorbents for the removal of cadmium and lead from aqueous solution: Adsorption mechanism and kinetic studies. (October 2016) - Kumar, K. Yogesh; Raj, T.N. Vinuth; Archana, S.; Prasad, S.B. Benaka; Olivera, Sharon; Muralidhara, H.B.
Graphical abstract: Highlights: SnO2 is prepared by simple and cost effective precipitation method. Residual concentration of heavy metal ions were determined by DPASV. SnO2 has high adsorption capacity for Cd (II) and Pb (II). Adsorption mechanisms of Cd (II) and Pb (II) on SnO2 are elucidated. SnO2 performs perfect regeneration capacity after multiple uses. Abstract: Adsorption studies of toxic metal ions Cd(II) and Pb(II) onto SnO2 nanoparticles are presented in this paper. SnO2 nanoparticles have been prepared via precipitation method and tested for heavy metal ions adsorption. Adsorbent is characterized by XRD, SEM, TEM and BET. SnO2 nanoparticles are proved to be effective adsorbents for the removal of Cd(II) and Pb(II) ions from solution. They exhibit good adsorption capacity and the adsorption data follow the Langmuir model. The maximum adsorption capacities of 1275.5 and 1265.8 mgg −1 are obtained for Cd(II) and Pb(II), respectively. Adsorption of both the metal ions is found to increase with the increase in temperature indicating exothermic nature of the adsorption process.